Profitability, Institutional Ownership, Size of the Board of Commissioners and Disclosure of Corporate Social Responsibility - Ni Putu Widya Adnyani; I Putu Sudana (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Corporate social responsibility disclosure is a way for companies to communicate with stakeholders regarding social and environmental impacts.This study aims to determine the effect of profitability, institutionalownership and board size on CSR disclosure. Stakeholder salience theory as the foundation in this study, indicates that stakeholders who have power can influence company activities, including in making CSR disclosures. The number of samples that met the criteria using the purposive sampling method were 132 observations of companies in the basic and chemical industry sectors listed on the IDX for the 2018-2021 period. The collected data were analyzed with multiple linear regression. The results of this study indicate that institutional ownership and profitability have no effect, while the size of the board of commissioners has an effect on CSR disclosure. The implications of this study show that of all stakeholders' salience, it was found that only the board of commissioners played an important role in influencing CSR disclosure.